1984
DOI: 10.1097/00004032-198412000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Pb by Human Skeleton and Comparative Metabolism of Pb and Alkaline Earth Elements

Abstract: Measurements of the retention of 47Ca and of 203Pb were made following their administration by intravenous injection. Translocation to bone was measured by gamma counting the feet of subjects. Uptake by bone of 203Pb was comparatively slow and extrapolation to the whole skeleton indicated that 20% of the dose had been taken up within 20 days. By time, a similar fraction of the dose had been excreted in urine. These results are consistent with Kehoe's (Ke61) long-term balance studies on 2 human subjects given s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 0 publications
4
35
0
Order By: Relevance
“…The second statement is consistent with the existing literature on the mechanism and kinetics of bone Pb/bone blood exchange [16][17][18][19][20][21][22][23]. The long half-life of Pb in bone is especially relevant to an understanding of the Pb content of the Beechey Island burials, which occurred early in the expedition.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The second statement is consistent with the existing literature on the mechanism and kinetics of bone Pb/bone blood exchange [16][17][18][19][20][21][22][23]. The long half-life of Pb in bone is especially relevant to an understanding of the Pb content of the Beechey Island burials, which occurred early in the expedition.…”
supporting
confidence: 85%
“…Individual metals are displayed using a color scale based on the maximum concentration of the metal; the scale is not normalized in such a way as to allow direct comparison of the concentrations of different metals. While it has been suggested that a detailed study of the Haversion canals in bone may provide a chronology of Pb accumulation [36], the existing literature [16][17][18][19][20][21][22][23] on the kinetics of Pb/bone exchange make it clear that the Pb distribution patterns within bone will provide a realistic chronology of uptake. The significance of the distribution of other metals must be uncertain, though the Beechey Island materials (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the EPA Integrated Exposure Uptake Biokinetic (IEUBK) model (9), the higher absorption values among adult males are applied to children up to 7 years old. The adult values for gastrointestinal lead uptake are fairly well validated using long-term mass balance studies (12,13), radioactive tracers (14)(15)(16)(17)(18)(19), and stable isotope tracers (20,21). Most adult subjects were males.…”
Section: Enmentioning
confidence: 98%
“…Data for laboratory animals indicate that fractional deposition on bone surfaces, as judged by the total skeletal content in the first few hours after injection, is similar for calcium, strontium, barium, and radium, despite the different excretion rates of these elements (Bligh and Taylor 1963;Kshirsagar et al 1966;Domanski et al 1969Domanski et al , 1980. Use of a common bone-surface deposition fraction for all four elements is also consistent with the limited human data, including: autoradiographic measurements of surface activity in bone samples taken at autopsy from subjects injected with radiocalcium at 0.6 d or longer before death (Riggs et al 1971, ICRP 1973; calcium and strontium concentrations in autopsy samples of bone from subjects injected with radiocalcium and radiostrontium at 3 h or longer before death (Schulert et al 1959); externally measured buildup and decline of injected radiocalcium over areas of the human body where bone activity is expected to predominate (Anderson et al 1970, Heard andChamberlain 1984); and external measurements of the peak skeletal content of intravenously injected 133m Ba in human subjects (Korsunskii et al 1981). Based on these data, it is assumed that 25% of calcium, strontium, barium, or radium leaving plasma is deposited on bone surfaces of the mature adult.…”
Section: Icrp Modelmentioning
confidence: 99%